Physiological responses of grapevines to environmental stresses - Dami, Imed Eddine, author; Stushnoff, Cecil, advisor; Smith, Danny, committee member; Morgan, Jack, committee member; Hughes, Harrison, committee member (Colorado State University. Libraries, 1997)
The field response of several grapevine (Vitis vinifera L) cultivars, grown at the Orchard Mesa Research Center, to methanol application on foliage and trunks was investigated. Sublethal methanol doses were determined as 90% for leaves and 100% for trunks. The application of these concentrations on grapevines during mid-summer did not affect sugar accumulation, photosynthesis, transpiration, stomatal resistance, yield components, nor bud cold hardiness as compared to untreated vines. Cold hardiness and endogenous levels of soluble sugars were monitored during the dormant season for Chardonnay and Riesling dormant buds and stem cortical tissues. Endogenous levels of glucose, fructose, raffinose, stachyose, but not sucrose were strongly associated with cold hardening, increasing from the onset of cold acclimation in August to maximum cold hardiness in December and January. During dehardening in March and April, levels of these sugars dropped as temperature increased. A high ratio of glucose and fructose to sucrose coincided with maximum cold hardiness, and a low ratio was associated with the dehardened condition in fall and spring. Neither cold hardiness nor soluble sugars of grape tissues were influenced by late harvest compared to harvest at normal fruit maturity. Various alginate- and sucrose-based cryoprotective treatments were tested under laboratory and field conditions for their capacity to increase freezing resistance by slowing deacclimation and delaying bud break of dormant grapevines. Early application of the treatments in mid-winter did not have a significant effect on cold hardiness of buds nor canes. However, over three years late winter and early spring field applications consistently increased freezing resistance of treated primary bud and cane tissues by up to SC and 7C, respectively, as compared to untreated grapevines. Under laboratory conditions, the bud break of treated cuttings was delayed by at least 4 phenological stages when compared to the control. In the spring, similar treatments were applied on ecodormant grapevines. Visual evaluations, on a weekly basis, resulted in bud break delay of several days (up to 10 days) of the treated vines as compared to the control. At harvest, the yield components and fruit composition were not affected in treated vines. These findings appear promising to reduce injury in viticultural areas where spring frost is a threat.
Keywords: Grapes -- Effect of stress on; Grapes -- Physiological effect